A STUDY OF THE EFFECT OF DISSOLVED CO2 AND NaCl TO THE FATIGUE RESISTANCE OF LOW CARBON STEEL AT ROOM TEMPERATURE AND OPEN SYSTEM - Iman Pangestu - (13713004 ), Prima
A riser pipe is a component used in oil and gas industries that is susceptible to corrosion-fatigue. Based on statistics, the most common failure mechanism caused by corrosion is initiated by the external environment. In addition, seawater nowadays is also becoming more acidic because of its reaction with CO2 from the air to form carbonic acid. This experiment represents a corrosion-fatigue attack on riser pipe material in a moving seawater environment. Material used in this experiment is a lowcarbon steel with 0.187 percent carbon. An artificial seawater is made by dissolving CO2 gas and 3.5% NaCl in a demineralized water. The testing is conducted at five loads: 394, 365, 331, 294, and 259 MPa, then continued at lower loads to determine its fatigue limit. The experiment resulted quantitative (SN diagram) and qualitative data (fractography). Results showed that the SN diagram obtained at air environment has a fatigue limit of around 195-200 MPa, but not for the SN diagram obtained at corrosive environment. The fatigue life measured at corrosive environment is lower than those measured at air, but only significant at lower loads. Fractography observation resulted in ratchet marks found on many fracture surfaces, suggesting that they failed because of high stress concentration. The high stress concentration supposedly caused by surface defects as a result of corrosive reaction, proven by the discovery of corrosion product and pits found on the specimen's surface.